Analisis Pasal 252 KUHP Baru Perspektif Hukum Islam dalam Pengembangan Teori Hukum - Puspitasari, Deny; Arzaqi, Nila (STAINI Press, 2025)
This study examines Article 252 of the New Criminal Code (KUHP) regarding its relevance and legal proof. The analysis is conducted from an Islamic law perspective using maqashid syariah, Quranic evidence, and Hadith, and compares it with the concepts of hudud, qisas, and ta'zir. Using a qualitative method based on library research with a descriptive-analytical approach, this research aims to support the development of Islamic legal theory that is harmonious with national law and relevant to the pluralism of Indonesian society. The discussion of Article 252 reveals the differences between Islamic law and positivistic approaches in dealing with witchcraft (santet). In Islamic law, witchcraft is considered a major sin that damages faith and social harmony, with proof based on witnesses, confessions, and indications in accordance with maqashid syariah. Meanwhile, the positivistic approach faces challenges in proving witchcraft due to its supernatural nature, making confessions as the primary evidence in Article 252 vulnerable to bias and subjectivity.